A systematic review and meta-analysis of Latent tuberculosis infection in Health care workers in Iran: Latent tuberculosis infection in HCWs - Firoozeh, Fahimeh; Firoozeh, Arezoo; Firoozeh, Farzaneh; Salmani, Abbas (Novelty in Biomedicine, 2022)
Background: Health care workers (HCWs) are more likely to get latent tuberculosis infection (LTBI) because of the direct contact they may have with patients and carriers. Therefore, this study aimed to assess the prevalence of LTBI in HCWs. Materials and Methods: In the present study, we searched from 1st 2010 to the end of 2021 in various databases such as; PubMed, Scopus, Web of sciences, and Google Scholar for studies presented LTBI in HCWS. After applying inclusion and exclusion criteria and quality assessment, obtained data were analyzed by Comprehensive Meta-analysis (CMV) software. Results: In total, 22 studies met the eligibility criteria to include in the present systematic review and metaanalysis. The combined prevalence of LTBI was reported by 25.9% (95% CI: 19.3-33.7). No publication bias was seen among studies included based on Eger’s regression test (p=0.04). Conclusion: Our study showed a high prevalence of LTBI in HCWs. Therefore, periodical screening of HCWs with Suitable tests is essential to prevent this high prevalence. According to the results of this systematic review and meta-analysis, the rate of LTBI in Iranian HCWs is high. Therefore, periodical screening and diagnostic tests such as TST are necessary for the timely diagnosis and treatment of these individuals to prevent changing LTBI to an active form of tuberculosis.